A novel approach on evolutionary dynamics analysis â A progress report - Zelinka, I. (Elsevier B.V., 2018)
In this paper, we discuss the possibility of unique mutual fusion of evolutionary algorithms, complex networks, strange dynamics and hidden attractors. As demonstrated in many research papers, evolutionary algorithms are capable of very complex tasks such as chaotic system control, identification or synthesis and vice versa; chaos can also be observed in the evolutionary dynamics, as originally demonstrated by various researchers. We propose a novel approach on how to analyze and control dynamic of the evolutionary algorithm and also discuss the possibility of strange dynamics analysis that can be a part of dynamic of evolutionary algorithms. In any words, we propose to understand algorithms as a discrete dynamical system that exhibits a wide spectrum of the behavior that can be controlled and analyzed. Â© 2017 Elsevier B.V.